2017
DOI: 10.1596/1813-9450-8050
|View full text |Cite
|
Sign up to set email alerts
|

The Misallocation of Pay and Productivity in the Public Sector: Evidence from the Labor Market for Teachers

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 35 publications
5
42
0
1
Order By: Relevance
“…However, the extent to which inequalities in achievement between poor and rich children can be explained by differential access to high quality schools and teaching is less understood. Some studies have quantified the impact of teachers on pupil achievement in Pakistan, or explored the importance of particular teacher characteristics in determining pupil outcomes in primary (typically children aged 5-9 years) or middle (aged 10-14 years) schools (Aslam & Kingdon, 2011;Rawal et al, 2013;De Talance, 2017;Bau & Das, 2017). These studies consistently point to the importance of teachers in improving student learning in Punjab, with teacher content knowledge and the 'process' of teaching, rather than the observed resumé characteristics of teachers being important determinants of pupil outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent to which inequalities in achievement between poor and rich children can be explained by differential access to high quality schools and teaching is less understood. Some studies have quantified the impact of teachers on pupil achievement in Pakistan, or explored the importance of particular teacher characteristics in determining pupil outcomes in primary (typically children aged 5-9 years) or middle (aged 10-14 years) schools (Aslam & Kingdon, 2011;Rawal et al, 2013;De Talance, 2017;Bau & Das, 2017). These studies consistently point to the importance of teachers in improving student learning in Punjab, with teacher content knowledge and the 'process' of teaching, rather than the observed resumé characteristics of teachers being important determinants of pupil outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher quality is important for improving student achievement (Rockoff 2004;Hanushek and Rivkin 2010;Chetty, Friedman, and Rockoff 2014;Bruns and Luque 2015). For example, the difference between a high and low quality teacher amounts to a difference of 0.36 standard deviations (SDs) in student test scores in Uganda (Buhl-Wiggers et al 2017), and a 0.54 SD difference in Pakistan (Bau and Das 2017). Unfortunately, researchers have found that a large proportion of teachers in developing countries are ill-prepared for teaching, lacking the requisite knowledge and skills to improve student achievement (Behrman et al 1997;Villegas-Reimers 1998;Ball 2000;Behrman, Ross, and Sabot 2008;Bruns and Luque 2015;Tandon and Fukao 2015;Bold et al 2017).…”
mentioning
confidence: 99%
“…In the United States, students in a class with an effective teacher advance 1.5 grade levels or more over a single school year, compared with just 0.5 grade levels for those with an ineffective one (World Development Report 2018). Similar effects of the quality of teachers on learning are also found in Ecuador, Uganda, Pakistan and India (Bau and Das 2017). Beteille and Evans (2019) find that some of the most effective interventions to improve student learning rely on teachers.…”
Section: Increasing the Social Value Of The Teaching Careermentioning
confidence: 69%